Scope and limitations of environmental fiscal control against the sustainable commercial exploitation of biodiversity in colombia (Revista cientifica In Vestigium Ire, 2019)
Megabiodiversity is currently closely related to the management of tangible and intangible resources that from scientific biosprospection generate important information and knowledge applied to biotechnological innovations, which are finally reflected in invention patents with a commercial vocation in the pharmaceutical, agri-food and cosmetic fields.Such events have required institutional challenges in Colombia, in terms of achieving sustainable exploitation of biodiversity and the establishment of fair conditions in the equitable participation of patent royalties that can be ended bytaking advantage of the information contained in genetic resources and traditional knowledge.In this sense, this qualitative research exercise presents a reflection on national policies far the development of biotechnology based on the sustainable exploitation of Biodiversity and the crisis of the State in terms of environmental fiscal control, highlighting the importance of the participation of the citizens as the maximum authority within the State, as well as the imperative need to join efforts with other living forces such as Universities, in arder to build, from the base, an integral transformation of the country's environmental policy.
Keywords: biodiversity; citizenship; environmental fiscal control; access to genetic resources; nagoya protocol